2012
DOI: 10.5552/drind.2012.1136
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Effects of Foreign Direct Investment in Terms of Slovak Republic and Wood-Processing Industry of Slovakia

Abstract: The presence of foreign direct investment in certain sectors or country determines several factorsthe determinants of foreign direct investment. The article analyzes the selected factors of FDI infl ows to the Slovak Republic and to the wood-processing industry in SR; it focuses primarily on assessing the contemporary situation of the business environment in Slovakia and investment incentives provided to foreign investors. The article also presents the development of foreign direct investment in Slovakia, in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…FDI by multinational corporations plays an important role in the transformation of former centrally planned economies into vibrant market systems, since it provides an inflow of capital, management skills, and jobs, alongside increasing exports and transfer of technology (Chidlow, Salciuviene & Young, 2009). Considering given localization of our research and existing literature from this region, authors Pavlínek and Smith (1998) Merková, Drábek & Jelačić, 2012). Another research realized in Slovakia has statistically confirmed that better business performance is significantly dependent on financing from foreign capital (Merková, Rajnoha & Dobrovič, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…FDI by multinational corporations plays an important role in the transformation of former centrally planned economies into vibrant market systems, since it provides an inflow of capital, management skills, and jobs, alongside increasing exports and transfer of technology (Chidlow, Salciuviene & Young, 2009). Considering given localization of our research and existing literature from this region, authors Pavlínek and Smith (1998) Merková, Drábek & Jelačić, 2012). Another research realized in Slovakia has statistically confirmed that better business performance is significantly dependent on financing from foreign capital (Merková, Rajnoha & Dobrovič, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other side, the wood-processing industry of Slovakia noted no innovation development focused on increasing the competitiveness of production and efficiency increasing. Positive is the labour productivity growth, the most significant in pulp and paper, where is recorded long-term growth above the average of industrial production, especially in periods with high inflows of FDI into the mentioned sector (Merková et al, 2012). Foreign capital firms, mostly multinationals, are a special category in the analysed sector.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Most empirical studies conclude that FDI contributes to both factor productivity and income growth in host countries; beyond what normally would trigger domestic investment, the fastest-growing countries are also the biggest FDI-host countries. Several previous research studies were dedicated to FDI issues in CEE countries (Rajnoha et al, 2018;Dudáš and Lukáč, 2014;Merková et al, 2012;Gauselmann et al, 2011;Dow and Ferenčíková, 2010;Chidlow et al, 2009;Rugraff, 2008). Horta et al (2016) demonstrated the impact of internationalisation and diversification strategies on the performance of construction industry companies.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The wood-processing industry in Slovakia is currently in a difficult situation, but there are still possibilities for better investment management and the potential for a positive impact on the performance of companies [13]. Quantitative analysis at the level of the wood-processing industry confirmed the significant impact of investment on the growth of sales and productivity; the subsequent analysis of the structure of value added showed a strong correlation between wages and value-added growth [14]. Also, according to several economic indicators, productivity growth and wages, the paper sector appears to be a sector with potential for the Slovak economy.…”
Section: Introductionmentioning
confidence: 95%